One More Time : What Are Institutions and How Do They Change? - Islam, Roumeen (World Bank, Washington, DC, 2018)
This paper defines institutions, presents their basic characteristics, and discusses forces for institutional change. It draws on a wealth of research and study by scholars in different fields and follows from the flagship 2002 World Development Report on this topic, including relevant new research since then that illuminates key issues. The definition of institutions includes rules and organizations (specifically rules guiding peoples’ actions). The paper emphasizes the diversity of institutions that can effectively perform similar functions, the arguments for and against standardization of institutions across specific transactions or groups, and the implications of these choices. It highlights the relationship between informal and formal institutions. It discusses forces for institutional change influencing all economies, ranging from external shocks (whether they be economic or weather-related shocks or driven by wars) to internal dynamics, such as those following population growth or compositional changes, and those following technological innovations. Many of these forces have a two-way relationship with institutions: they are affected by them and, in turn, influence whether and when they change. A special section is devoted to institutional transplants and their effectiveness. The paper concludes with a discussion of whether and under what conditions institutional change can be externally directed and the lessons for aid donors.